Approaches and Models for Evaluating the Agility Degree of Agile Software Development Methods - Hesham Ali Saad; Mohamed Abedulrashid Ghali (International Journal of Computers and Informatics, 2023)
Agile Software Development (ASD) is the umbrella for several other popular methods such as Scrum, XP, Feature Driven Development, DSDM, Crystal, and others. ASD methods are based on developing software products using short iterations, each iteration is like a short project. Also, ASD methods use “inspect and adapt” practices to adjust the project plan. This paper presents a review of approaches, models, and frameworks for evaluating the agility degree of ASD methods. Each approach, model, or framework is based on a set of practices, features, or events that support agility. This review can help managers of software projects to choose the appropriate ASD method for their projects.